2015
DOI: 10.1038/jp.2015.146
|View full text |Cite
|
Sign up to set email alerts
|

NICU discharge planning and beyond: recommendations for parent psychosocial support

Abstract: Parents will interact with a multitude of teams from various disciplines during their child's admission to the neonatal intensive care unit. Recognition of the emotional stressors experienced by these parents is a first step in working to provide the crucial support and parenting skills needed for bonding and caring for their infant from admission through discharge and beyond. Family-centered care involves time-sensitive two-way communication between parents and the multidisciplinary team members who coordinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
124
1
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(132 citation statements)
references
References 38 publications
(65 reference statements)
0
124
1
7
Order By: Relevance
“…19 Family-centered care practice includes open visitation for parents to be present, and nurses facilitating interaction and communication between infants and their parents at birth or as soon as possible after. 7,8 …”
Section: Interaction Communication and Visitationmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Family-centered care practice includes open visitation for parents to be present, and nurses facilitating interaction and communication between infants and their parents at birth or as soon as possible after. 7,8 …”
Section: Interaction Communication and Visitationmentioning
confidence: 99%
“…2 Johnson et al 6 described FCC as a philosophy of care where the family's role is recognized and respected as being essential. Stress and negative outcomes are reduced through parent/family involvement in care activities, communication and education, 7,8 group and individual therapy and support systems, 9 and consideration of age-specific needs (eg, needs of a teenage mother). 3 In the NICU context, family often refers to the neonate, the mother, and the father, but it can include grandparents, extended family members, significant other(s) identified by the mother/father, and the sibling(s).…”
mentioning
confidence: 99%
“…Several key categories of support for parents with babies in the NICU have been identified that are well aligned with I/ECMH practice. These include parent emotional support, parent education, and child development support (Benzies, Magill-Evans, Hayden & Ballantyne, 2013;Purdy, Craig, & Zeanah, 2015). I/ECMH interventions have been shown to result in changes in parent-child interactions, parental mental health status, and child behavior and physiological status in the population of newborn intensive care unit graduates.…”
Section: Nicu and I/ecmhmentioning
confidence: 99%
“…Parents of these babies are likely to experience greater emotional stress, depression, and uncertainty about their baby's future, as well as financial stress than do parents of term infants (Blackburn, 2010;Boyova, Kenner, 2012;Fraley, 1989;Gennaro, Grisemer, Musci, 1992;Purdy, Craig, & Zeanah, 2015). Examples of parental stress related to hospital experiences include "the sudden nature of the situation, the separation from the child, and the lack of information concerning the prognosis" (Habersaat, Pierrehumbert, Forcada-Guex, Nessi, & Ansermet, 2014, p. 458;Singer, Salvator, Guo, Collin, Lilien, Baley, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation